Tensile properties of composite metal foam and composite metal foam core sandwich panels. (November 2021) - Marx, Jacob; Rabiei, Afsaneh
Steel-steel composite metal foam (SS-CMF) and composite metal foam core sandwich panels (SS-CMF-CSP) were manufactured and tested under quasi-static tension. The SS-CMF-CSP were manufactured by attaching stainless steel face sheets to a SS-CMF core using solid-state diffusion bonding. SEM imaging was used to inspect the microstructure of SS-CMF and compare it to that of SS-CMF-CSP. The results indicate a cohesive bond line at the interface of the core and the face sheets. The bare SS-CMF samples had an ultimate tensile strength between 75–85 MPa and a failure strain between 7.5–8%. The normalized tensile strength of the SS-CMF was approximately 24 MPa/(g/cm 3 ), 410% higher than other comparable metal foams, with a specific energy absorption of 0.95 J/g under tension. The uniform porosities and strong bonding between the sphere wall and matrix seem to be the strengthening factor of SS-CMF under tension when compared to other metal foams. The ultimate tensile strength of the SS-CMF-CSP was 115% stronger than the bare SS-CMF at 165 MPa with an average failure strain of 23%. The normalized strength of the SS-CMF-CSP was 52% higher than the bare SS-CMF. The modulus of elasticity was approximated using the rule of mixtures for the SS-CMF and the SS-CMF-CSP and the experimental results were found to lie within the calculated upper and lower bounds.